Molecular characterization of Glutathione S-transferase in two eel species, Monopterus cuchia (Hamilton) and Monopterus albus (Zuiew) - Devi, Papari; Baruah, Chittaranjan; Sharma, D.K. (Asian Journal of Biological and Life Sciences, 2020)
The present investigation has been carried out for DNA isolation, sequencing, sequence analysis, tertiary structure prediction and phylogenetic analysis of Glutathione S-transferase from two freshwater synbranchid eel species of the genusMonopterusin different states of Northeast India (Assam and Manipur). Glutathione S-transferase is potentially used as a biochemical marker of aquatic pollution and they are the decisive indicators of the toxic effect. The GST gene sequences ofM. cuchiais more G: C rich thanM. albusand the GST gene ofM. albusis more A: T rich than that ofM. cuchia. The instability index (II) value of GST enzyme of the present study ranged from 49.26 to 52.67, which classifies the GST protein as unstable. The phylogenetic analysis of GST gene revealed that,M. cuchiaandM. albusformed two separate clades with high bootstap separation 98% and 100% in ML and MP tree respectively clearly indicates the possibility for existence of two sub-species inM. cuchia. The MP phylogeny of GST gene also revealed genetic diversity withinM. albusat 73% bootstrap separation. Some of the samples ofM. albusandM. cuchiain the GST gene phylogenetic tree revealed the possibility of interbreeding or hybridization in theMonopterusspecies. The predicted 3D structure of GST will reveal more insights on GST activity inM. albusandM. cuchiain order to reveal the detailed detoxification mechanism freshwater eels.
Keywords: Glutathione S-transferase; Monopterus. Northeast India; synbranchid